GS&E journal > Mechanical analysis and characterization of IGUs with different silicone sealed spacer connections - Part 2: modelling - Chiara Bedon (Challenging Glass Conference, 2020)
Insulated Glass Units (IGUs) typically consist of two glass layers, either monolithic and/or laminated sections, that mechanically interact via an hermetically-sealed air (or gas) cavity, and a series of linear spacer connections along their edges. In this paper, based on the experimental tests for small-scale IGU joints under pure shear and IGU prototypes in bending discussed in “Part I”, a special care is spent for the Finite Element (FE) numerical characterization and analysis of these composite systems, with a focus on the actual mechanical properties and load-bearing mechanism for the involved components. Major advantage is taken from the full 3D solid geometrical description of the connection components and the gas cavity infill. The actual role of both primary and secondary sealant layers is first assessed. Further support is derived from analytical calculations for the connection efficiency assessment, based on the adaptation of simplified formulations of literature. Finally, a calculation example is proposed to assess the magnitude of load sharing phenomena, based on FE numerical and analytical calculations for selected configurations.